2013
DOI: 10.1149/05801.0271ecst
|View full text |Cite
|
Sign up to set email alerts
|

Nafion-1,2,3-Triazole Composite Membrane for Fuel Cell

Abstract: The mechanical stability of Nafion -1,2,3-triazole composite membrane and conductivity and cell performance in the single cell were investigated by dynamic elastic modulus and fuel cell measurement system, respectively. The thermal stability of the composite membrane was increased than that of Nafion 112. The viscosity was also improved after activation treatment of the membrane. The maximum conductivity of 0.07 S/cm and maximum power density of 582 mW/cm 2 were obtained at the single cell test. A long term st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, we z E-mail: kim.jedeok@nims.go.jp found that Nafion -1,2,3-triazole composite membranes are stable even against treatment with boiling water and sulfuric acid. 26,28 Under autoclave conditions, 1,2,3-triazole can react with 1-and 2-propanol contained in Nafion solution due to the catalytic effect of the Nafion acid side chain, leading to Nafion -propyl-1,2,3-triazole composites (Scheme 1). In this paper, Nafion -propyl-1,2,3-triazole composite membrane was prepared and characterized in detail by FT-IR, MAS NMR, TGA, dynamic elastic modulus, TEM, elementary analysis, water-uptake, ion exchange capacity (IEC), conductivity, and cell performance.…”
mentioning
confidence: 99%
“…On the other hand, we z E-mail: kim.jedeok@nims.go.jp found that Nafion -1,2,3-triazole composite membranes are stable even against treatment with boiling water and sulfuric acid. 26,28 Under autoclave conditions, 1,2,3-triazole can react with 1-and 2-propanol contained in Nafion solution due to the catalytic effect of the Nafion acid side chain, leading to Nafion -propyl-1,2,3-triazole composites (Scheme 1). In this paper, Nafion -propyl-1,2,3-triazole composite membrane was prepared and characterized in detail by FT-IR, MAS NMR, TGA, dynamic elastic modulus, TEM, elementary analysis, water-uptake, ion exchange capacity (IEC), conductivity, and cell performance.…”
mentioning
confidence: 99%